KAJIAN POLA INTERAKSI KERUANGAN SENTRA USAHA PENGASAPAN IKAN DI DESA WONOSARI, KABUPATEN DEMAK - Fajar Hadhiyanto Wibowo; Sri Rahayu (Teknik PWK (Perencanaan Wilayah Kota), 2017)
The availability of human needs are not all available in one place, but scattered unevenly in different regions. So it will trigger a spatial interaction between one place to another. This happens in the business center of curing fish in Wonosari, Demak. These fish fogging activities triggered the spatial interactions between Wonosari the areas of raw material suppliers and territories marketing of products. This study was intended to determine the pattern of spatial interaction that occurs in the business center of curing fish in Wonosari. With the approach of quantitative research and quantitative research methods descriptive. The analysis used the analysis flow of business activities curing fish and spatial interaction pattern analysis. Analytical results from this research that there are two aspects that led to the occurrence of spatial interaction in business activities curing fish in Wonosari namely the aspect of input (supply of raw material, production equipment, transfer of knowledge) and the output aspect (marketing of products). From the results of analysis show that Juwana is an area of major raw material suppliers of the business center of curing fish in Wonosari, so the most powerful spatial interaction in the aspect of input occurs with the region. In the aspect of output (marketing), the largest market area is to Demak with large sales index to the region by (100%). This shows that the marketing of smoked fish products still dominated sales to the local region. So the conclusion is very strong spatial interaction with other areas occur on aspects of input and output interaction for the most powerful aspects of the local area itself.